2020
DOI: 10.1039/d0re00041h
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the direct synthesis of dimethyl ether from CO2 rich synthesis gas: closing the loop between experimental investigations and model-based reactor design

Abstract: Kinetic modeling, model-based optimization and experimental validation for the direct DME synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…Furthermore, the consistency of this effect throughout the entire investigated gas flow range can be attributed to a constant selectivity towards DME. A detailed description of the observed phenomena can be found elsewhere 28. Model predictions in this operational range demonstrate the high level of agreement between the simulated and measured values, also showing a smooth mapping and the ANN's ability to generalize and make predictions for unseen data within the model's validity range.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…Furthermore, the consistency of this effect throughout the entire investigated gas flow range can be attributed to a constant selectivity towards DME. A detailed description of the observed phenomena can be found elsewhere 28. Model predictions in this operational range demonstrate the high level of agreement between the simulated and measured values, also showing a smooth mapping and the ANN's ability to generalize and make predictions for unseen data within the model's validity range.…”
Section: Resultsmentioning
confidence: 61%
“…At low temperatures, the low reaction rates lead to overall low conversion and yield. Hence, resulting in small DME amounts in the product gas and thus in a reduced measuring accuracy 28. Therefore, the deviations of both models can be mainly attributed to experimental measurement uncertainties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the composition of the catalyst bed, previous investigations 14, [20][21][22][23] have shown on the basis of simulated and experimental data that optimization can lead to signicant enhancement of the process performance. For instance, in the studies of Peláez et al 15 and Peinado et al 24 the authors showed that for CO 2 rich synthesis gas a signicant increase in the performance is achieved by increasing the CZA-to-g-Al 2 O 3 ratio.…”
Section: Catalyst Bed Composition and Congurationmentioning
confidence: 99%